Brain lateralization and neural plasticity for musical and cognitive abilities in an epileptic musician - Trujillo-Pozo, Isabel; Martín-Monzón, Isabel; Rodríguez-Romero, Rafael (Frontiers in Human Neuroscience, 2013)
The use of intracarotid propofol procedure (IPP) when assessing musical lateralization has not been reported in literature up to now. This procedure (similar to Wada Test) has provided the opportunity to investigate not only lateralization of language and memory functions on epileptic patients but also offers a functional mapping approach with superior spatial and temporal resolution to analyze the lateralization of musical abilities. Findings in literature suggest that musical training modifies functional and structural brain organization. We studied hemispheric lateralization in a professional musician, a 33 years old woman with refractory left medial temporal lobe epilepsy. A longitudinal neuropsychological study was performed over a period of 21 months. Before epilepsy surgery, musical abilities, language and memory were tested during IPP by means of a novel and exhaustive neuropsychological battery focusing on the processing of music. We used a selection of stimuli to analyze listening, score reading, and tempo discrimination. Our results suggested that IPP is an excellent method to determine not only language, semantic and episodic memory, but also musical dominance in a professional musician who may be candidate for epilepsy surgery. Neuropsychological testing revealed that right hemisphere’s patient is involved in semantic and episodic musical memory processes, whereas her score reading and tempo processing require contribution from both hemispheres. At 1-year follow-up, outcome was excellent with respect to seizures and professional skills, meanwhile cognitive abilities improved. These findings indicate that IPP helps to predict who might be at risk for postoperative musical, language and memory deficits after epilepsy surgery. Our research suggests that musical expertise and epilepsy critically modifies long-term memory processes and induces brain structural and functional plasticity.